Marketing Students Take on University Library as Client in Experiential Learning Assignment - Mary Kelly; Matthew Schirano; Lisa Thornell (Marketing Libraries Journal)
In this collaboration between university librarians and faculty, advertising students were given the unique opportunity to treat the university library as a client in a rebranding initiative. This partnership allowed students to work in agency-style teams, simulating a real-world professional setting where they were responsible for developing a comprehensive branding strategy aligned with the library’s newly implemented strategic plan. Acting as consultants, they conducted research, analyzed the library’s current branding, and identified areas for improvement, all while considering the library’s goals, values, and desired image within the university community. This experiential learning project provided students with an immersive experience that went beyond traditional classroom learning. By engaging directly with a real client (the university library), they gained hands-on experience with the dynamics of the advertising industry, including client communication, project management, creative strategy, and ad development. Furthermore, the project generated numerous actionable recommendations for the library’s branding and outreach efforts, demonstrating the practical value of the collaboration.